Characteristics of constitution and traditional Chinese medicine syndrome distribution in patients with allergic rhinitis complicated with asthma - ZHANG Jintao, LI Yue, YANG Qintai, YANG Hongzhi, ZHOU Qilin, CHEN Hongjie, KE Qianshan, WANG Xiaoying, DAI Min (Xin yixue)
Objective To analyze the distribution characteristics of constitution and traditional Chinese medicine syndrome of allergic rhinitis patients complicated with asthma， aiming to provide basis for integrated traditional Chinese and western medicine treatment for allergic rhinitis complicated with asthma. Methods After preliminary screening of traditional Chinese medicine constitution identification of allergic patients in the allergic WeChat applet of Gamma on Cloud， patients with allergic rhinitis complicated with asthma or other allergic diseases receiving multi-disciplinary diagnosis and treatment of Department of Allergy of the Third Affiliated Hospital of Sun Yat-sen University from January 2020 to May 2024 were selected. General data such as gender and age， constitution of traditional Chinese medicine and traditional Chinese medicine syndrome of allergic rhinitis patients complicated with asthma were collected and retrospectively analyzed. According to the new concept of “allergic 5A grading diagnosis and treatment” proposed by the team from Department of Allergy， all patients were divided into three groups： 2A patient group （ allergic rhinitis complicated with asthma）， 3A patient group （allergic rhinitis complicated with asthma， and any of atopic dermatitis， allergic conjunctivitis or food allergy） and 4A or 5A patient group （allergic rhinitis complicated with asthma， and any two or three of atopic dermatitis， allergic conjunctivitis or food allergy）. Results There were 42 patients in the 2A group， 18 males and 24 females， aged （26.4±16.6） years old， 40 patients in the 3A patient group， 19 males and 21 females， aged （25.0±15.5） years old， and 8 patients in the 4A or 5A patient group， 5 males and 3 females， aged （15.5±13.2） years old， respectively. In the 2A patient group， the most frequent constitutions were yang-deficiency constitution （n = 17）， qi-deficiency constitution （n = 14） and inherited special constitution （n = 11）. In the 3A patient group， the most common constitutions were qi-deficiency constitution （n = 23）， inherited special constitution （n = 16） and yang-deficiency constitution （n = 9 ）. In the 4A or 5A patient group， the most prevalent constitutions were qi-deficiency constitution （n = 6） and inherited special constitution （n = 4）. Fisher’s exact test found that there were differences in the distribution of yang-deficiency constitution among all groups （all P < 0.05）. In terms of traditional Chinese medicine syndromes， the most common traditional Chinese medicine syndromes in the 2A patient group were yang deficiency with congealing cold syndrome （n = 10）， wind-cold-dampness syndrome （n = 8） and lung-spleen qi deficiency syndrome （n = 6）. The most common traditional Chinese medicine syndromes of 3A patients were lung-spleen qi deficiency syndrome （n = 12）， yang deficiency with congealing cold syndrome （n = 7） and wind-cold-dampness syndrome （n = 6）. The most common traditional Chinese medicine syndrome of 4A or 5A patients was lung-spleen qi deficiency syndrome （n = 5）. There were differences in the distribution of traditional Chinese medicine syndromes among the three groups （all P < 0.05）. The difference between 2A patients and 4A or 5A patients was statistically significant （P < 0.001）. The difference between 3A patients and 4A or 5A patients was also statistically significant （P < 0.001）. Conclusions The most common constitutions of allergic rhinitis patients complicated with asthma are yang-deficiency constitution， qi-deficiency constitution and inherited special constitution. The most prevalent traditional Chinese medicine syndromes are yang deficiency with congealing cold syndrome， wind-cold-dampness syndrome and lung-spleen qi deficiency syndrome. There are differences in the distribution of constitution and traditional Chinese medicine syndrome among patients with different grades of allergic rhinitis complicated with asthma.